"Eu sou o caminho, a verdade e a vida": a exclusividade do cristianismo e a capacidade para o diálogo com as religiões - Brandt, Hermann (2013)
Beginning with the apparent incompatibility between the affirmation of the exclusiveness of Christianity and the capacity for dialogue with the other religions, the author expounds and briefly discusses three models: the exclusivist, the inclusivist and the pluralist, criticizing the latter because of its static view of the relationship among religions. In a second moment, the author expounds his own theses about the relationship between exclusivism and the capacity to dialogue, first using as a base the concept of mission examined from the perspective of the science of religion, and then from the Christian perspective starting with the simultaneity of the exclusivist, inclusivist and pluralist postures on an existential level and a theological questioning of the exclusiveness “of Christianity”.